1. The problem statement, all variables and given/known data Integrate √(x2(x+3)) from -3 to 0. 0 ∫√(x2(x+3)) dx -3 2. The attempt at a solution Here is what I did: √(x2(x+3)) = x√(x+3) Let u=x+3, du=dx, x=u-3 Insert the bounds and change the bounds to: 0 to 3. x√(x+3)= (u-3)√(u) = u3/2-3u1/2 Thus we have: 3 ∫(u3/2-3u1/2) du 0 Finally: (2u5/2)/5-(2u3/2) from 0 to 3. Thus I get: -4.15. However the correct answer is positive 4.15. I know the answer should be positive but what I don't understand is why I'm getting a negative answer. Please help. Thanks in advance.